Treatment pattern and health care resource utilization for Taiwanese patients with migraine: a population-based study - Wang, Yen-Feng; Wang, Shuu-Jiun; Huang, Yao Hsien; Chen, Yung-Tai; Yen, Yu-Chun; Shia, Ben-Chang; Tsai, Ching-Wen; Chan, Hoi-Fong; Panni, Tommaso; Dell’Agnello, Grazia (Frontiers in Neurology, 2023)
Objectives: Given the substantial disease burden, appropriate and effective management of migraine is a public health priority. To gain insights into real-world migraine management practices in Taiwan, current treatment patterns, costs, and health care resource use were assessed. Methods: This was a retrospective, longitudinal study using the Taiwan National Health Insurance Research Database. Included patients had an initial diagnosis of migraine (defined using International Classification of Diseases codes) between 1 January 2013 and 31 December 2017. Data analyzed included demographics; the use, number, and type of acute and preventive medications; and drug and medical services costs. Data were stratified according to migraine type (chronic [CM] or episodic [EM] migraine). Results: A total of 312,718 patients were included in the analyses: 53,992 (17.3%) had CM and 258,726 (82.7%) had EM. Most patients (81.7%) had used acute and/or preventive medications; acute medications used more frequently than preventive medications (78.0% vs. 20.2%). Acute medications were used by 81.6% and 77.3% of patients with CM and EM, respectively. Commonly used acute medications were acetaminophen (68.8%), ergots (49.4%), and non-steroidal anti-inflammatory drugs (38.4%); the use of triptans (6.0%), tramadol (3.1%), and other opioids (0.2%) was less common. A total of 28.6% and 18.5% of patients with CM and EM, respectively, used preventive medications. Flunarizine (68.9%), propranolol (40.7%), and topiramate (16.0%) were the most commonly used preventive medications. Most patients had used 1–2 acute or preventive medications, with the use of ≥3 acute or preventive medications more common in patients with CM than EM. Average total medical cost per annum was 4,169 New Taiwan Dollars (NTDs) per CM patient and 2,928 NTDs per EM patient, with CM patients having higher costs associated with medical service utilization and acute medication use. Conclusions: These real-world data suggest unmet needs for Taiwanese patients with migraine, including under-utilization of preventive medications and greater costs and health care resource use for patients with CM versus EM. These findings provide important information on treatment patterns, cost, and health care resource use for patients with migraine in Taiwan.